BUILDING PLURALIST ATTITUDE IN DOING ISLAMIC EDUCATION AT HIGHT SCHOOL AND MADRASAH - Moh. Haitami Salim (Al-Albab, 2013)
The pluralist attitude is often associated with acknowledging and appreciating ethnic and religious differences which are, in fact, plural. The plurality of ethnicity is a natural process because no one can choose to be born into parents of a certain group. Meanwhile the plurality of religion is the result of someone’s choice of faith and is part of the human rights. A person cannot change their ethnicity but it is possible for them to change their religion. Nor can religious conversion change a person’s ethnicity, as in the case in West Kalimantan where a Christian ethnic Dayak converts to Islam to become a Malay, for example. It is why religion and ethnicity are plural, so appreciating and acknowledging the plurality as inevitability is known as a “pluralist” attitude. In Islam, especially in the instruction of Islamic education at school, or madrasah, pluralist attitude should be extended to include not only the attitude of acknowledging and appreciating ethnic and religious differences, but also the awareness of the existence of variants of the plurality in a religion, ethnicity and even in a family. Building a pluralist attitude among people with the same faith and ethnicity is often overlooked, that later led to an attitude of ambiguity, thus being friendly towards people of a different religion or ethnicity, but being hostile when dealing with fellow religious or ethnic members. The phenomenon is clearly visible in the dispute between the followers of Sunni and the Shi’ite in which the leaders are brothers. To ensure that the instruction of Islamic education is able to build a pluralist attitude on learners, we need to start building the ability of teachers to develop the curriculum, prepare the lesson plans, develop contextual learning materials and use varied learning strategies and methods. Keywords: Instruction of Islamic education, Pluralist attitude, School, Madrasah